Pengembangan Media Video Pembelajaran Teknik Menjahit Mata Pelajaran Teknik Menjahit Tata Busana X Di SMK - Clarisya, Assa; Mariah, Siti; Inayah, Desy Tri (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
The purpose of this research is to create an instructional video teaching basic sewing techniques to fashion students in grade X. Another objective is to assess the effectiveness of the video and understand student responses. The research method employed is Research and Development (R&D) using a Four-D validator approach. The validator includes media experts, subject matter specialists, and feedback from a small scale of six students and a limited scale of 30 participants. Research findings indicate that the 9-minute instructional video covering basic techniques such as blanket stitch, whip stitch, back stitch, and chain stitch can be utilized both online and offline. The video media is deemed suitable with expert ratings of 85% for media experts and 86% for subject matter specialists. With student responses reaching 93% in the small scale and 84% in the limited scale, indicating a "strongly agree" category, it can be concluded that the instructional video for sewing techniques is highly recommended for use in basic sewing subjects.